Pengaruh Pemahaman Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak PPh Final 0,5 UMKM Kelurahan Kebon Kacang (Lembaga Pengembangan Kinerja Dosen, 2024)
This research investigates the influence of tax understanding and tax sanctions on the compliance of Micro, Small, and Medium Enterprises (MSMEs) taxpayers subject to the 0.5% Final Income Tax in Kebon Kacang Village. Low tax compliance among MSMEs remains a concern despite their large contribution to the national economy. This study aims to analyze whether tax understanding and tax sanctions significantly affect taxpayer compliance, both individually and simultaneously. Using a quantitative approach, data were collected through questionnaires distributed to 77 respondents determined using the Slovin formula from a population of 337 MSMEs. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS 26. The results indicate that tax understanding has a positive and significant effect on taxpayer compliance, and tax sanctions also show a positive and significant relationship with compliance. Simultaneously, both variables significantly influence taxpayer compliance with a determination coefficient of 56.6%. These findings imply that improving taxpayers’ understanding and implementing consistent sanctions can strengthen taxpayer compliance, particularly among MSMEs. Policymakers are encouraged to enhance tax education programs and optimize the enforcement of tax regulations.